Prognosis of patients with severe hyponatraemia is related not only to hyponatraemia but also to comorbidities and to medical management: results of an observational retrospective study. Issue 1 (December 2016) - Krummel, Thierry; Prinz, Eric; Metten, Marie-Astrid; Borni-Duval, Claire; Bazin-Kara, Dorothée; Charlin, Emmanuelle; Lessinger, Jean-Marc; Hannedouche, Thierry
Abstract Background The true cause of death in severe hyponatraemic patients remains controversial. The present study aimed to analyse the relationship between comorbidity, medical management and prognosis in severe hyponatraemic patients. Methods Medical records of all patients hospitalised in our institution in 2012 with a plasma sodium ≤120 mmol/l were retrospectively analysed. Results One hundred forty-seven of 64 723 adult patients (0.2 %) were identified with severe hyponatraemia. In-hospital mortality rate was 24.5 and 50.3 % after a median follow-up of 431 days. Patients with plasma sodium <110 mmol/l had less comorbidity (Charlson Comorbidity Index 2.2 ± 1.9 vs. 4.0 ± 3.1 (plasma sodium 110–115 mmol/l) and 4.2 ± 3.1 (plasma sodium 116–120 mmol/l);P = .02)) and a small trend for less mortality, respectively 40.0, 51.2 and 52.3 % (P = .64). At discharge, nonsurvivors and survivors had similar plasma sodium with 58.3 % of nonsurvivors being normonatraemic. Urine analysis was performed in 74.2 % of cases and associated with lower in-hospital mortality (20.2 % vs. 36.8 %, P = .05). In multivariate Cox analysis, mortality was significantly associated with plasma sodium normalisation (HR 0.35, P < 0.001), urine analysis (HR 0.48, P = .01), Charlson Comorbidity Index (HR 1.23, P < .001) and serum albumin (HR 0.88, P < .001). Conclusion Mortality in severe hyponatraemia appears mainly due to comorbidities although the latter are potentiated by hyponatraemia itself and its management thereby exacerbating the risk of death.